2017
DOI: 10.1080/13816810.2017.1354382
|View full text |Cite
|
Sign up to set email alerts
|

Association of HTRA1 rs11200638 with age-related macular degeneration (AMD) in Brazilian patients

Abstract: Age-related macular degeneration is a multifactorial disease that can lead to vision impairment in older individuals. Although the etiology of age-related macular degeneration remains unknown, risk factors include age, ethnicity, smoking, hypertension, obesity, and genetic factors. Two main loci have been identified through genome-wide association studies, on chromosomes 1 and 10. Among the variants located at the 10q26 region, rs11200638, located at the HTRA1 gene promoter, has been associated with age-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Another Chinese study showed a 7.6-fold increased risk in subjects with the A allele, with smoking status compounding the risk to 15.7fold [15]. Studies in Middle East [18], India [19], and Brazil [17] have shown similar results. Individuals with the AG and AA genotype have been found to have a 2.2-and 8.7-fold higher risk of developing AMD, respectively, when compared with those who carry the GG genotype [26].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Another Chinese study showed a 7.6-fold increased risk in subjects with the A allele, with smoking status compounding the risk to 15.7fold [15]. Studies in Middle East [18], India [19], and Brazil [17] have shown similar results. Individuals with the AG and AA genotype have been found to have a 2.2-and 8.7-fold higher risk of developing AMD, respectively, when compared with those who carry the GG genotype [26].…”
Section: Discussionmentioning
confidence: 80%
“…Patients with the AA genotype were more prone to have AMD by nearly 26-fold. The association remained strong after data adjustment with [12,[17][18][19][22][23][24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, different genotype methods were applied in included studies, we tried to in each method, whether associations may exist in our analysis, we found some positive results in some methods (such as in AA vs. GG model: OR = 7.00, 95% CI = 5.84-8. 39, P heterogeneity = 0.677 about sequencing, Figure 7A; OR = 7.52, 95% CI = 2.05-27.68, P heterogeneity < 0.001, P = 0.002 about TaqMan; OR = 4.30, 95% CI = 2.51-7. 35, P heterogeneity = 0.073, Figure 7B) (Table 3).…”
Section: Subgroup Analysismentioning
confidence: 98%
“…Age-related macular degeneration (AMD) is a prevalent multifactorial disorder of the central retina and is the leading cause of vision loss in individuals over the age of 50. [1,2] AMD is divided into 2 basic clinical classification: early (visual symptoms are inconspicuous) and late (severe loss of vision is usual) 2 stages. [3] Based on the pathological features, AMD is classified into dry (nonexudative) and wet (exudative) 2 forms.…”
Section: Introductionmentioning
confidence: 99%